Changes in atherosclerotic aorta of rabbit fed with high cholesterol diet: The effect of vitamin E [YUKSEK KOLESTEROLLU DIYET ILE ATEROSKLEROZ OLUSTURULAN TAVSAN AORTASINDA MEYDANA GELEN DEGISIKLIKLER: E VITAMINI'NIN ETKISI] - (:unkn) unknown (My University, 1996)
Background and design: Atherosclerosis call be triggered by a multiplicity of risk factors, but its common feature is intimal thickening caused by the proliferation of smooth muscle cells which have migrated from the media. Hypercholesterolemia is one most important risk factors of the disease. Proteinkinase C is a pivotal enzyme which relays signals of proliferation and differentiation in smooth muscle cells. The protective role of vitamin E as an antioxidant in cardiovascular disease has long been recognized. RRR-α-Tocopherol was shown to inhibit the proteinkinase C activity and proliferation of cultured smooth muscle cells independently of its antioxidant properties. Methods: In the present study, we investigated the molecular changes in aortic smooth muscle cells of rabbits fed with high cholesterol diet. In addition, we investigated if we would observe a parallel relation between proteinkinase C activity, smooth muscle cell proliferation and vitamin E in an experimental model of atherosclerosis at microscopical and biochemical levels ex-vivo. Results: The group receiving a cholesterol-rich diet had serum cholesterol levels of 875 ± 573 mg/dL, the group received cholesterol rich-diet + vitamin E 811 ± 300 mg/dL and the control group 64 ± 11 mg/dL. Serum vitamin E levels were 3.2 ± 1.3 μg/mL for the control group, 9.8 ± 2.9 μg/mL for the cholesterol group, and 122.6 ± 42.7 μg/mL for the cholesterol + vitamin E group. Our light microscopy results showed that hypercholesterolemia induced a prominent intimal thickening. Proteinkinase C activities of the aortic homogenates were 10.55 ± 2.12 for the cholesterol group, 9.41 ± 0.94 for the cholesterol + vitamin E group and 5.42 ± 1.89 Δ absorbance/min/μg protein for the control group. Vitamin E was shown to protect from smooth muscle cell proliferation at microscopical level and partially effect the signal transduction cascade of smooth muscle cell proliferation.
Keywords: Atherosclerosis; Proteinkinase C; Vitamin E